Rancang Bangun Aplikasi Projek Wedding Monitoring Berbasis Web Dengan Metode Extrem Programing (Studi Kasus: Gayatri Wedding) - Afrizaldo (CV. Shofanah Media Berkah, 2024)
Current technological developments have a good impact on humans, in this case especially for most companies, where technology can facilitate human activities. One of the implementations of information technology that is very widely applied to companies is information systems, where one of them is a wedding organizer monitoring application. There is research on monitoring wedding organizers, but the results of this study have not provided opportunities for companies to monitor wedding projects online. Research on online marriage monitoring applications is important because it provides benefits in providing information quickly, and makes it easier for agencies to be able to monitor ongoing wedding projects. The resulting wedding monitoring web application can provide solutions to existing problems. So with this application, relevant agencies can use it to improve performance and time efficiency in timing and monitoring a wedding project.